(3bWYI ef cJGH aj Yde GdUQas
(3ChdgG (B:s
(3EYde CjgG GdeJYde Cf GdJUQja Ci daX (B( (3GdJUQja (B) (3GdPi gh eQcH ef GdJGA hGdUGO hGdjGA hGdaGA ai GddZI Ci ai dSGf GdYQH GdJZjQ s
(3BNQgG (B:s
(3eeG RGO Ydi KdGKI CNQa QHGYjkG cGf Ch KdGKjkG eRjOkG ajg jchf HRjGOI GdgGA Ci JGA GdJCfjK s
(3HChdg bUjOI ddTjN Rjf GdOjf GHf GdhQOi ai HjY hTQGA bWYI CQVs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdUfGYI hGdCWYeIs